EPR response of anhydrite crystal (CaSO4) for dosimetry of gamma photon beams - Cano, Nilo F. (2021)
An anhydrite (CaSO4) natural sample was studied as possible dosimeter for low and high gamma doses using the technique of electron paramagnetic resonance (EPR). EPR spectrum showed signals due to (SO3)(-), (SO4)(-) radicals and O center. The anhydrite sample was irradiated with gamma rays with low-dose ranges typical for medical therapy (1-20 Gy) up to high-dose of about 70 kGy. The EPR centers due to (SO3)(-) and (SO4)(-) exhibited a linear dose response in the dose range from 1 Gy to 500 Gy, whilst the 0 center presented a supra-linear dose response in the range of 50 to 5 kGy.